Strategic Sport Communication : Traditional and Transmedia Strategies for a Global Sports Market - Coombs, W. Timothy; Harker, Jennifer L. (Routledge, 2022)
"Authors Coombs and Harker provide step-by-step guidance on how the strategic communication process-an integration of marketing communication, public relations, and advertising-can be applied to sports communication for individual athletes, teams, and leagues. The book is founded on the premise that the strategic communication process in sport communication is grounded in understanding the fans and sources of revenue. Looking at sports globally, it offers readers the traditional multi-step, linear approach to strategic communication message development along with the Transmedia Narrative Transportation method, a non-linear approach that centers on narratives to engage target audiences and urge them to contribute their own material to messaging. With case studies and practical examples, it also highlights additional issues such as race and gender, social media, ethics, and athlete health. It is an ideal text for undergraduate and graduate courses in public relations or strategic communication and sport communication. An online instructor's manual accompanies the text, including lecture slides; a sample strategic sports communication plan; a test bank; links to key web sites that discuss sports and sports communication concerns; links to case studies with class discussion prompts; sample assignments; a sample course syllabus, and suggestions for further reading"--